No Evidence for Memory Decontextualization across One Night of Sleep - Jurewicz, Katarzyna; Cordi, Maren Jasmin; Staudigl, Tobias; Rasch, Björn (Frontiers in Human Neuroscience, 2016)
Sleep after learning strengthens memory consolidation. According to the active system consolidation hypothesis, sleep supports the integration of newly acquired memories into cortical knowledge networks, presumably accompanied by a process of decontextualization of the memory trace (i.e., a gradual loss of memory for the learning context). However, the availability of contextual information generally facilitates memory recall and studies on the interaction of sleep and context on memory retrieval have revealed inconsistent results. Here we do not find any evidence for a role of sleep in the decontextualization of newly learned declarative memories. In two separate studies, 104 healthy young adults incidentally learned words associated with a context. After a 12-h retention interval filled with either sleep or wakefulness, recall (Experiment 1) or recognition (Experiment 2) was tested with the same or different context. Overall, memory retrieval was significantly improved when the learning context was reinstated, as compared to a different context. However, this context effect of memory was not modulated by sleep vs. wakefulness. These findings argue against a decontextualization of memories, at least across a single night of sleep.